Homeostatic control of metabolic and functional fitness of T(reg) cells by LKB1 signaling - Yang, Kai (Nature, 2017)
Regulatory T cells (T(reg) cells) play a pivotal role in the establishment and maintenance of immunological self-tolerance and homeostasis(1,2). Transcriptional programming of regulatory mechanisms facilitates T(reg) cell functional activation in the prevention of diverse types of inflammatory responses(3,4). How T(reg) cells orchestrate their homeostasis and interplay with environmental signals remains poorly understood. Here we show that liver kinase B1 (LKB1) programs proper metabolic and functional fitness of T(reg) cells in the control of immune tolerance and homeostasis. Mice with T(reg)-specific deletion of LKB1 developed a fatal inflammatory disease characterized by excessive T(H)2-dominant responses. LKB1 deficiency disrupted T(reg) cell survival and mitochondrial fitness and metabolism, but also induced aberrant expression of immune regulatory molecules including the negative co-receptor PD-1, and TNF receptor (TNRF) superfamily proteins GITR and OX40. Unexpectedly, LKB1 function in T(reg) cells was independent of conventional AMPK signaling or the mTORC1-HIF-1α axis, but contributed to the activation of β-catenin signaling for the proper control of PD-1 and TNFR proteins. Blockade of PD-1 activity reinvigorated the suppressive capability of LKB1-deficient T(reg) cells in the repression of T(H)2 responses and the interplay with thymic stromal lymphopoietin (TSLP)-primed dendritic cells (DCs). Thus, T(reg) cells employ LKB1 signaling to coordinate their metabolic and immunological homeostasis and to prevent apoptotic and functional exhaustion, thereby orchestrating the balance between immunity and tolerance.